South American Nothochrysinae (Neuroptera, Chrysopidae): I. Description of Nothochrysa ehrenbergi sp. nov. - Catherine A. Tauber (ZooKeys, 2019)
A new species, Nothochrysa ehrenbergi sp. nov., is described from Chile; it is the first species of Nothochrysa to be reported from the Southern Hemisphere and only the second from the New World. The genus now contains six extant species as well as two species known from late Oligocene and Miocene fossils. An updated catalog of the valid Nothochrysa species is presented, and three nomina dubia are discussed. The inclusion of the new species in Nothochrysa is well supported by morphological features. However, it and other species currently in the genus also share significant features with Archaeochrysa, an older genus of Nothochrysinae which is known only from the Eocene (Ypresian) to the late Oligocene. It therefore appears that N. ehrenbergi is among the least derived Nothochrysa species, and that the separation of Archaeochrysa from Nothochrysa is open to question and further examination.